Legitimasi Putusan Lembaga Adat dalam Sistem Hukum Nasional: Studi terhadap Peraturan Perundang-Undangan di Indonesia - Nanda Firdaus Puji Istiqomah (Jurnal Hukum Lex Generalis, 2025)
The legitimacy of customary institution decisions in the national legal system still faces various challenges, especially the lack of formal recognition and limited execution in state courts. Although customary law is recognized in the constitution, its implementation is often not in sync with national law. This study highlights the need for regulatory harmonization so that customary institution decisions have clearer and more effective legal force in the national legal system.